2012
DOI: 10.1002/ijc.27765
|View full text |Cite
|
Sign up to set email alerts
|

Risk of skin cancer and other malignancies in kidney, liver, heart and lung transplant recipients 1970 to 2008—A Swedish population‐based study

Abstract: Organ transplant recipients are at increased risk of a wide range of malignancies, especially cutaneous squamous cell carcinomas (SCC). Few previous population-based studies have quantified and compared cancer risks according to graft type and with long-term follow-up. Using nationwide Swedish registers, we identified 10,476 recipients transplanted from 1970 to 2008 and followed them for cancer occurrence. Relative risks of cancer in comparison with the general population were expressed as standardized inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
310
16
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(361 citation statements)
references
References 52 publications
25
310
16
10
Order By: Relevance
“…In our cohort it was not possible to assess its association due to incomplete data. Similarly, higher incidence of PTLD has been observed in some recent studies 5,6 . There are still only a few data in the literature evaluating other types of malignancies in HTRs.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our cohort it was not possible to assess its association due to incomplete data. Similarly, higher incidence of PTLD has been observed in some recent studies 5,6 . There are still only a few data in the literature evaluating other types of malignancies in HTRs.…”
Section: Discussionsupporting
confidence: 71%
“…Most of the available data show elevated risk of malignancy in organ transplant recipients 5,6 . In our study, we analysed the demographic characteristics, frequency and histopathological spectrum of tumours in 603 patients after HT.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 39 were excluded, as they comprised 3 duplicate studies, 2 studies not written in English, 1 review, 21 from which the SIR and 95% CI could not be calculated, 10 studies on hospital-based cohorts and 2 on irrelevant topics. Finally, 22 cohort studies contained in 18 studies were included in the present meta-analysis (8)(9)(10)(11)(12)(13)(14)(15)(16)(22)(23)(24)(25)(26)(27)(28)(29)(30). The main characteristics of the studies included are presented in Table I.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…However, the distribution of cancer types in Asian RTRs differed from that in non-Asian RTRs. Numerous studies have shown that in Western countries, RTRs are at greater risk of developing NMSC (16,25,26). By contrast, NHL as well as renal and bladder cancer had the highest SIRs in Hong Kong (14), and kidney cancer was the most common cancer type in Taiwan (13) and Japan (24).…”
Section: Heterogeneity ----------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation